Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1748-0221/14/10/c10025
|View full text |Cite
|
Sign up to set email alerts
|

Recent Doppler backscattering applications in Globus-M tokamak

Abstract: A: Recently, a four-frequency Doppler backscattering (DBS) system was installed on the Globus-M tokamak. In addition to the classical DBS application for determining the mean plasma rotational velocities, DBS was used for the investigation of different plasma oscillatory processes in the spherical Globus-M tokamak. Application of various DBS data processing allowed us to reveal and investigate plasma oscillations, such as geodesic acoustic mode, limit cycle oscillations and Alfvén modes. It has been shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The radial scale of the observed flow is estimated to be 4 cm [42,46]. This scale is close to the radial wavelength of the zonal flows [41].…”
Section: Limit Cycle Oscillationssupporting
confidence: 56%
See 2 more Smart Citations
“…The radial scale of the observed flow is estimated to be 4 cm [42,46]. This scale is close to the radial wavelength of the zonal flows [41].…”
Section: Limit Cycle Oscillationssupporting
confidence: 56%
“…The GAM frequency was also investigated in different locations and it was determined that no significant change of its values was present. Experiments with a four frequency DBS scheme confirmed the narrow localization of GAM [42]. Only the peripheral DBS channel could register GAM oscillations near the normalized minor radius 0.95, whereas the other channels did not detect oscillations exceeding the background level at the GAM frequency.…”
Section: Geodesic Acoustic Modementioning
confidence: 69%
See 1 more Smart Citation
“…Filament characteristics have been studied extensively over the years using various diagnostic techniques [ 7 ]. One such diagnostic technique (unconventional though it may be for this purpose) is the Doppler backscattering (DBS) method [ 8 ], which was initially employed at the spherical tokamak Globus-M [ 9 , 10 , 11 , 12 , 13 ] and later the ASDEX Upgrade tokamak [ 14 ] for the purpose of studying filaments. It has been observed that the DBS signal reacts to backscattering from filaments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it had been used for the first time to investigate the properties of Alfven eigenmodes such as amplitude, location and their dependence on the plasma parameters which proved a fruitful venture [15], however the possibility to detect these instabilities using DBS was demonstrated earlier in work [17]. The localization and detection of different phenomena on the Globus-M tokamak was determined [18]. Unfortunately, due to the limitations of the DBS system itself not everything could be investigated or analysed.…”
Section: Introductionmentioning
confidence: 99%